Web-Based Learning Innovation in Economics Education: Leveraging Google Sites to Boost Interactivity and Conceptual Understanding - Yulia Suriyanti; Avelius Dominggus Sore; Dessy Triana Relita; Yopinus Bobi; Munawar Thoharudin; Mukhamad Zulianto (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
The integration of digital learning environments has become increasingly important in economics education, particularly in facilitating students’ understanding of abstract and interconnected concepts. Nevertheless, previous studies on Google Sites-based learning media have primarily focused on technical feasibility and usability, while the pedagogical relationship among instructional design, student engagement, and conceptual understanding remains underexplored. This study aimed to develop and evaluate Google Sites-based learning media and examine its role in fostering engagement and conceptual understanding in economics instruction. The study employed a Research and Development (R&D) approach using the 4D model, consisting of the define, design, develop, and disseminate stages. The participants included tenth-grade students at SMA Nusantara Indah Sintang and two expert validators. Data were collected through classroom observations, expert validation instruments, and student response questionnaires using Likert scales and were analyzed descriptively through feasibility and validity assessments. The findings indicated that the developed media achieved high validity scores from media experts (90%) and subject-matter experts (89%), while student responses reached 92.5%, reflecting high levels of usability, interactivity, and cognitive engagement. The results further demonstrate that multimedia integration, structured navigation, and interactive learning activities contribute to improved conceptual understanding in economics learning. The novelty of this study lies in its integrative instructional perspective, which positions student engagement as a pedagogical mechanism linking digital instructional design and conceptual learning outcomes within web-based learning environments.